NUP98/11p15 translocations affect CD34+ cells in myeloid and T lymphoid leukemias. Issue 7 (July 2015) - Crescenzi, Barbara; Nofrini, Valeria; Barba, Gianluca; Matteucci, Caterina; Di Giacomo, Danika; Gorello, Paolo; Beverloo, Berna; Vitale, Antonella; Wlodarska, Iwona; Vandenberghe, Peter; La Starza, Roberta; Mecucci, Cristina
Highlights NUP98 translocations are early leukemic lesions which affect a CD34+/CD133+ precursor. The NUP98/RAP1GDS1 fusion affected different lineages in AML and T-ALL. MDS/AML and T-ALL showed additional myeloid and T cell-lineage specific mutations, respectively.